2008
DOI: 10.2214/ajr.07.3145
|View full text |Cite
|
Sign up to set email alerts
|

MDCT of the Breast

Abstract: Our results confirm and strengthen the importance of all imaging parameters and not one in particular. Dynamic MDCT can be used in the evaluation of selected patients with suspected breast tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…In 2009, approximately 190,000 new cases of breast cancer were diagnosed in the United States and over 40,000 women died of the disease [ 8 ] ; the incidence in Europe is 94.3 per 100,000 women [ 9 ] . While mammography is the most efficient way to screen for primary breast cancers, the ability to spot primary breast lesions and metastases on routine CT scans is important, as this may lead to a diagnosis before the patient would have otherwise come to medical attention [ 10 ] , and improve the accuracy of staging for patients with a breast cancer diagnosis.…”
Section: Breast Cancermentioning
confidence: 99%
“…In 2009, approximately 190,000 new cases of breast cancer were diagnosed in the United States and over 40,000 women died of the disease [ 8 ] ; the incidence in Europe is 94.3 per 100,000 women [ 9 ] . While mammography is the most efficient way to screen for primary breast cancers, the ability to spot primary breast lesions and metastases on routine CT scans is important, as this may lead to a diagnosis before the patient would have otherwise come to medical attention [ 10 ] , and improve the accuracy of staging for patients with a breast cancer diagnosis.…”
Section: Breast Cancermentioning
confidence: 99%
“…▪ Inoue M et al conducted MDCT examinations using a comparable protocol in 149 patients with suspicion of a breast carcinoma [14]. All 173 detected breast lesions were histologically verified.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of CT in diagnostic imaging of the breast shown by Uematsu T et al [13], Perrone A. et al [15], and Inoue M et al [14] is taken into consideration in the current development of CT systems specifically designed for breast examinations. The first dedicated CT systems for the breast are currently being introduced by 2 companies (Koning Corporation, New York, USA; CT Imaging GmbH, Erlangen, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Recognized side effects of these procedures include nipple deformity, necrosis, and periareolar anesthesia in some cases (20%) (21)(22)(23) . There are many advanced studies and investigations for early detection of breast carcinoma, but all the investigations carry a certain percentage of false negative results in detecting early breast carcinoma, even advanced investigations like MR imaging with different contrast materials are not 100% accurate in excluding early breast carcinoma (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and this support the advice of this study treating older patients with ductectasia (when breastfeeding is not anticipated) by surgical excision of the major lactiferous ducts (Hadfield operation), in trial to find coexistent ductal carcinoma in situ that may not be detected by mammography nor by ultrasound study of the breast. This study concluded that conservative management of ductectasia of the breast by antibiotics does not relief symptoms.…”
Section: Discussionmentioning
confidence: 99%